1992
DOI: 10.1016/0014-5793(92)81112-y
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels from the Bacillus subtilis plasma membrane incorporated into planar lipid bilayers

Abstract: Fusion of Bacillus subtllis plasma membrane vesicles with planar lipid bilayers ind uced the appearance of discrete current fluctuations characteristic oi" ion channels. These channels showed a wide range ofconductances and kinetic behaviors. In 300 mM KCI, their condueumces ranged from a Few hundreds of pS to more than l aS, and most of them exhibited several sub.states. The channels poorly discriminated between small univalent onions and cations. Some of them showed voltage dependence and most of them presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Channel Activity in Planar Bilayers-High conductance, low selectivity channels were routinely observed upon fusion of B. subtilis vesicles with planar bilayers, in agreement with the observations by Alcayaga et al (41). Incorporation of a vesicle invariably led to the appearance of several conductances, ranging from about 0.1 to 1.5 nS (100 mM KCl), some of which clearly represented substates of others.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Channel Activity in Planar Bilayers-High conductance, low selectivity channels were routinely observed upon fusion of B. subtilis vesicles with planar bilayers, in agreement with the observations by Alcayaga et al (41). Incorporation of a vesicle invariably led to the appearance of several conductances, ranging from about 0.1 to 1.5 nS (100 mM KCl), some of which clearly represented substates of others.…”
Section: Resultssupporting
confidence: 77%
“…300 l were withdrawn from the cis chamber and replaced with 300 l of 3 M KCl to favor fusion and to establish a transmembrane salt concentration gradient. Mostly inside-out B. subtilis membrane vesicles, prepared as described (41), containing approximately 5-20 g of protein were then added to the cis side, and the chambers were stirred at intervals until incorporation occurred. Activity was monitored at a few voltages for a short time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for the presence of ion channels in the B. subtilis plasma membrane was also obtained by Alcayaga et al (1) in electrophysiological studies using fusions of plasma membrane vesicles with planar lipid bilayers. The channels detected in these studies showed a wide range of conductances and kinetic behaviors, suggesting that more than one channel-forming protein operates in B. subtilis.…”
supporting
confidence: 56%
“…lowing an osmotic downshock Levina et al, 1999 . In B. subtilis, the presence of ion-conducting pores that respond to mechanical forces has been demonstrated through electrophysiological studies. These channels display conductances ranging from a few hundred pS to more than 3 nS and most exhibit complex gating kinetics, suggesting that at least some are composed of subunits that Ž function cooperatively Alcayaga et al, 1992;Sz-. abo et al, 1992 .…”
Section: Expulsion Of Compatible Solutes: Protection Against Extreme mentioning
confidence: 99%